(untitled) (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Azadirachta indica, Gymnema sylvestre, Momordica charantia, Syzygium cumini, and Trigonella foenum-graecum are known for their antidiabetic effects; however, molecular mechanism/s have not been evaluated. We have attempted to elucidate a possible mechanism, namely, effect on peroxisome proliferator-activated receptor-g expression of these plant extracts using 3T3-L1 adipocytes. Materials and Methods: 3T3 L1 fibroblasts were initially differentiated into adipocytes, following which RNA was extracted and reverse transcribed to cDNA for evaluation of PPARγ expression. Relative expression was normalized using GAPDH. Relative messenger RNA expression level was calculated according to ΔΔCT method and compared with Pioglitazone, a known insulin sensitizer. Results: M. charantia, S. cumini, and G. sylvestre showed an increase in PPARγ expression as compared to Control cells. Pioglitazone also showed 2.5-fold increase in PPARγ expression. Of these three plant extracts, hydroalcoholic extract of M. charantia showed maximum PPARγ expression with 4.3-fold increase which was statistically significant compared to control and reference standards. Discussion: Activation of PPARγ leads in improvement of insulin sensitivity through binding of synthetic drugs resulting in a decrease in insulin and glucose levels in patients with diabetes. Conclusion: Our data thus demonstrates that M. charantia, G. sylvestre, and S. cumini can be considered as PPAR modulators, acting through the PPAR signaling pathway resulting in enhanced transcription during adipocyte differentiation. This could be beneficial in the management of diabetes and its long-term complications with lesser toxicities.